How student paramedics navigate a changing UK healthcare landscape. (2nd September 2020) - Lees, Carolyn; Hutchison, Trudy; White, Alison; Lotto, Robyn
Abstract : Background: Paramedics have witnessed a huge shift in their role as providers of prehospital emergency care, although little is known about how student paramedics manage the competing demands they face in practice. Aim: To explore how student paramedics experience the changing healthcare landscape. Method: Semi-structured, focus groups and thematic content analysis was adopted. A purposive sample of student paramedics at different stages of their diploma preparatory training were invited to participate in focus group interviews. Findings: Participants considered that other services and the public perceived the purpose of emergency paramedics as largely a traditional one, as a service to transport patients to hospital. This appears to influence how they manage complex clinical situations. Student paramedics' clinical decision-making is frequently influenced by the emotional environments in which they work, combined with difficult communication with patients and a lack of support from the various professional groups involved in patient care. Conclusion: This study has highlighted the complexity of situations that student paramedics find themselves in while making decisions, which has important implications for paramedic educators and those supporting them in practice.